Analysis of Mechanical Quality of Nickel-Base Superalloy Machined by Short Electric Arc - Liu, Hongsheng; Zhou, Jianping; Yu, Qing (Asian Journal of Chemistry, 2014)
It is a trial for machining GH4169 nickel-base super alloy by short electric arc machining. Since the theory is not complete, so prepare the experiment from the aspect of the parameters of the material removal rate, roughness of the finished surface, micro-hardness and heat-affected layer etc., which help to find the regulation of specimen surface quality on the different processing power parameters. Analyzing the alloying degree of cut tool surface based on the EDAX. Analyze the microstructure of the workpice surface by using scanning electron microscopy (SEM). Machining the GH4169 nickel-base super alloy by short electric arc machining technology can get satisfactory finished surface quality.